ANALISIS MIKRO EKONOMI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Siti Sara; Annisa Ilmi Faried; Rahmad Sembiring; Anggia Ramadhan (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze macroeconomic variables with a focus on exports, government expenditure, consumption, investment, the number of MSMEs, imports, and gross domestic product. This research is a quantitative research with data used in the form of time series data sourced from the Ministry of Cooperatives, MSMEs, and the World Bank. The data analysis technique used in this study is Simultaneous Equations. The results stated that in Simultaneous Equation I, the variable of government expenditure partially has a positive and significant effect on the variable of gross domestic product, while the variable of export, consumption, and import partially has a positive but not significant effect. Meanwhile, the variables of exports, government spending, consumption, and imports together affect the variables of gross domestic product. Simultaneous Equation II variables, the number of MSMEs partially has a negative and significant effect on import variables, and the gross domestic product variable partially has a positive and significant effect on import variables. Meanwhile, the investment variable partially has a positive but not significant effect on the import variable. Meanwhile, the variables of the number of MSMEs, gross domestic product, and investment together affect the import variable